2007
DOI: 10.1097/wno.0b013e31814b2845
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Edema, Cystoid Macular Edema, and Elevated Vascular Endothelial Growth Factor in a Patient With POEMS Syndrome

Abstract: A 48-year-old man with polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome had bilateral optic disc edema (ODE), bilateral cystoid macular edema (CME), anasarca, and elevated serum vascular endothelial growth factor (VEGF). This is the first reported example of ophthalmoscopic, angiographic, and optical coherence tomographic evidence of the combination of ODE and CME in this syndrome. This combination of features suggests that the ODE in this condition may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 18 publications
5
39
0
Order By: Relevance
“…Visual field testing usually demonstrates enlargement of the blind spot, 125,291 although arcuate defects are also described. 24,52,94 FA typically shows late optic disk leakage and may also demonstrate petaloid leakage consistent with CME. OCT may also confirm the presence of CME or macular detachment.…”
Section: Clinical Presentationmentioning
confidence: 86%
See 2 more Smart Citations
“…Visual field testing usually demonstrates enlargement of the blind spot, 125,291 although arcuate defects are also described. 24,52,94 FA typically shows late optic disk leakage and may also demonstrate petaloid leakage consistent with CME. OCT may also confirm the presence of CME or macular detachment.…”
Section: Clinical Presentationmentioning
confidence: 86%
“…64 The most common ocular finding in POEMS syndrome is bilateral optic disk edema (ODE), occurring in 29e73% of patients. 34,38,45,52 Kaushik et al, 125 in the largest study to date, found ODE in 17 of 33 patients (52%). Of note, five (29%) of the patients had asymptomatic ODE at the time of initial examination, leading the authors to advocate screening ophthalmologic examinations for all patients diagnosed with POEMS.…”
Section: Clinical Presentationmentioning
confidence: 94%
See 1 more Smart Citation
“…7 Alternatively, the optic nerve swelling may be related to increased vascular permeability and serum vascular endothelial growth factor or cytokine levels, as seen in a few cases where patients presented concurrently with macular edema. 8,9 A recent retrospective case series suggests that papilledema may be an independent risk factor for POEMS-related mortality. 10 Therefore, POEMS should be kept on the differential for bilateral optic nerve swelling.…”
mentioning
confidence: 98%
“…7 A retrospective case series looking at ocular findings in POEMS found that the most common visual field defects at initial ophthalmological assessment were bilaterally enlarged blind spots (75%, n ¼ 8), followed by general constriction (n ¼ 1), and nasal step defects (n ¼ 1). 8 Initial assessment showed good mean visual acuity, at 20/20 OD and 20/25 OS.…”
mentioning
confidence: 98%